Evidence for Impaired Hepatic Vitamin K1 Metabolism in Patients Treated with N-Methyl-Thiotetrazole Cephalosporins - Bechtold, H; Andrassy, K; Jähnchen, E; Koderisch, J; Koderisch, H; Weilemann, L S; Sonntag, H-G; Ritz, E (Thrombosis and Haemostasis, 1984)
In 8 patients on no oral intake and with parenteral alimentation, administration of cephalosporins with N-methyl-thiotetrazole side chain (moxalactam, cefamandole), was associated with prolongation of prothrombin time, appearance in the circulation of descarboxy-prothrombin (counter immunoelectrophoresis and echis carinatus assay) and diminution of protein C. Acute administration of 10 mg vitamin Ki was followed by the transient appearance of vitamin K1 2,3-epoxide, indicating an impaired hepatocellular regeneration of vitamin K1 from the epoxide. Impaired hepatic vitamin K1 metabolism, tentatively ascribed to the N-methyl-thiotetrazole group, is one (but possibly not the only) cause of bleeding complications and depression of vitamin K1dependent procoagulants in patients treated with the new class of cephalosporins.
Keywords: Cephalosporins; Hemostasis; Vitamin K; Descarboxyprothrombin; Protein C